2006
DOI: 10.2111/05-167r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and Grazing Exclusion Effects on New Mexico Shortgrass Prairie

Abstract: Vegetative differences and changes were evaluated over a 6-year period (1999-2004) on adjoining conservatively grazed and grazing-excluded (22 years) shortgrass rangelands in northwestern New Mexico. Autumn total perennial grass and blue grama (Bouteloua gracilis [Willd. ex Kunth] Lag. Griffiths) standing crop did not differ on grazed and grazing-excluded areas when data were averaged across years. There were no long-term differences in vegetation basal cover or composition between the grazed and grazing-exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
(8 reference statements)
5
9
0
Order By: Relevance
“…We found that the structure of the plant community was different among GE5, GE7, and continuous grazing plots, but it was similar between GEO7 plots and continuous grazing plots. This phenomenon was consistent with experimental results obtained from a New Mexico short-grass prairie (Holechek et al, 2006). Stable species richness and similar complexity level mean a similar competition situation in plant communities, which might be the reason why the plant community was similar between long-term grazing exclusion and continuous grazing pastures in GEB5, Grazing exclusion below 5 years; GE5, Grazing exclusion 5 years; GE7, Grazing exclusion 7 years; GEO7, Grazing exclusion over 7 years; TN, Total nitrogen; AN, available nitrogen; TOC, total organic carbon; AP, available phosphorus; AK, available potassium; BD, bulk density.…”
Section: Discussion the Relationship Between The Optimum Duration Of Grazing Exclusion And The Succession Of Plant Communitysupporting
confidence: 92%
“…We found that the structure of the plant community was different among GE5, GE7, and continuous grazing plots, but it was similar between GEO7 plots and continuous grazing plots. This phenomenon was consistent with experimental results obtained from a New Mexico short-grass prairie (Holechek et al, 2006). Stable species richness and similar complexity level mean a similar competition situation in plant communities, which might be the reason why the plant community was similar between long-term grazing exclusion and continuous grazing pastures in GEB5, Grazing exclusion below 5 years; GE5, Grazing exclusion 5 years; GE7, Grazing exclusion 7 years; GEO7, Grazing exclusion over 7 years; TN, Total nitrogen; AN, available nitrogen; TOC, total organic carbon; AP, available phosphorus; AK, available potassium; BD, bulk density.…”
Section: Discussion the Relationship Between The Optimum Duration Of Grazing Exclusion And The Succession Of Plant Communitysupporting
confidence: 92%
“…; Holechek et al. ). Five decades of grazing exclusion in shortgrass steppe induced only modest community shifts (Milchunas et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Holechek et al. ). After 23 yr of implementing grazing intensities that varied from light to heavy, Hyder et al.…”
Section: Introductionmentioning
confidence: 98%
“…Differences between 2013, 2014, and 2016 in initial body weights are likely due to a consistent single source with a limited spring calving period in the first two years, compared to sale barn cattle from multiple unknown origins in the third year. Range pastures were unequally sized, ranging from 5 to 16 ha across years; consequently, various numbers of animals were assigned to those pastures to provide for up to 50% utilization, as a moderate grazing intensity [14,15], during the anticipated grazing season to end in mid-March (30 d Every year, immediately prior to grazing, a sample was hand-clipped to ground level from a 0.5 m 2 area in each of three visibly representative areas in each pasture [5], and dried in a forced-air oven at 60 • C for 48 h [5]. These samples were submitted for estimation of CP and fiber-based components by near-infrared spectroscopy (NIRS) at Ward Laboratory (Kearney, NE, USA) using a calibration developed for grass hay by the NIRS Consortium (https://www.nirsconsortium.org/; accessed on 11 June 2021).…”
Section: Test Description Management and Data Collectionmentioning
confidence: 99%
“…There was no difference between pastures in forage mass again in 2016 (Table 3). Weather data for 2014-15 are included in Table 2 to show at least a temporary alleviation of the drought in 2015 to promote native grass growth for grazing in late winter 2015-2016 (Table 3) [14,15,23]. Much earlier planting of triticale, coupled with greater precipitation (Table 2), led to greater forage mass in those pastures as well.…”
Section: Monthly Forage Massmentioning
confidence: 99%